2019
DOI: 10.1029/2018gl081193
|View full text |Cite
|
Sign up to set email alerts
|

How the Inhomogeneity of Wet Sea Salt Aerosols Affects Direct Radiative Forcing

Abstract: Sea salt aerosols were assumed to be homogeneous spheres in most climate models. However, observations show that sea salt particles are inhomogeneous during the deliquesce and crystallization processes. Using a two‐layer sphere model, we found that backscattering of solar radiation associated with sea salts is underestimated in homogeneous sea salt models. The Community Earth System Model is used to assess the inhomogeneity effect on direct radiative forcing. For global climate model simulation, the inhomogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…In that study, superellipsoids resembling rounded cubes, spheres, and rounded octahedra as well as distortions of these base solids by changing the aspect ratio were considered. Sea‐salt aerosol with a water coating was investigated in regard to the depolarization ratio (Bi, Lin, Wang, et al., 2018), and in regard to the impact on radiative forcing (Wang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In that study, superellipsoids resembling rounded cubes, spheres, and rounded octahedra as well as distortions of these base solids by changing the aspect ratio were considered. Sea‐salt aerosol with a water coating was investigated in regard to the depolarization ratio (Bi, Lin, Wang, et al., 2018), and in regard to the impact on radiative forcing (Wang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(2018), only superspheroids with roundness parameter being equal to or greater than 1.0 were employed in simulations for modeling dust aerosols. Note that superspheroids with the roundness parameter (<1.0; not shown) were found useful for modeling dry sea‐salt aerosols (Bi, Lin, Wang, et al., 2018; Z. Wang et al., 2019). Because the superspheroidal model has one more degree of freedom as compared to the spheroidal model, the superspheroidal model allows the possibility to constrain the particle geometry in a relatively large shape space.…”
Section: Model and Methodsmentioning
confidence: 99%
“…According to Lin et al (2018), only superspheroids with roundness parameter being equal to or greater than 1.0 were employed in simulations for modeling dust aerosols. Note that superspheroids with the roundness parameter (<1.0; not shown) were found useful for modeling dry sea-salt aerosols (Bi, Lin, Wang, et al, 2018;Z. Wang et al, 2019).…”
Section: Superspheroidal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In marine environments, the influence of the RH is crucial to calculate the morphology and the refractive index of sea salts. Wang et al [14] reported that the inhomogeneity effect can cause up to 10% radiative forcing of sea salts. Therefore, an accurate assessment of the impact of inorganic salt shapes on optical properties and hence on the radiation field is still demanded.…”
Section: Introductionmentioning
confidence: 99%